Specific climatization of swine maternity: ethological evaluation of lactating females - Dela Ricci, Gisele; Berto, Dirlei Antonio [UNESP]; Dalla, Osmar; Sousa, Rafael Teixeira de; Tonon, Elder; Titto, Cristiane Goncalves (Univ Federal Ceara, Centro Ciencias Agrarias, 2018)
The experiment was carried out during the summer at UNESP in Botucatu. Eight females swines of the Landrace and Large White breed were randomly assigned according to the order of calving. The behavior was evaluated in the first week of lactation in the morning, afternoon and night periods. The environment of the maternity was sealed by plastic canvas. For the climatization were used six fans and two water sprinklers on the roof. Environmental temperatures were monitored by dry / wet bulb thermometers and black globe (Tg) with readings every five minutes, over the course of five days. The body temperature of the animals was measured with the aid of the digital thermometer. The environments with enrichment and control were compared, and the behavior of the females was performed with the aid of an etogram. The behavior of the animals was evaluated using the chi-square test (X-2), using the FREQ procedure of SAS version 9.1.2 (SAS Inst. Inc., Cary, NC). Litter, stereotyped, breathing, feeding, water consumption and movement differed statically among treatments, with a significant improvement in the well-being of the females in the climatization environment, mainly due to the decrease in the ambient temperature, where the temperature averages in the climatized area were of 17 and 18 degrees C and 32, 34 degrees C and control, with lower respiratory frequencies, with averages of 38 and 79 beats per minute and improved breathing in the three periods. It is concluded that the use of ventilators internally and sprinklers of water on the roof externally, improved the thermal comfort and the welfare of the swine.
Keywords: water; welfare; observation; swine; fans